Development of Hindi word identification in noise test for school aged children - Bhagat, Himadri; Khemka, Srabanti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Word identification in noise is crucial for effective communication in everyday environments. For children, the ability to identify words in noisy conditions directly impacts language development, learning, and social interaction. This study aimed to develop and standardize Hindi word identification in noise test for children (HWINT-C) and evaluate its performance among school aged typically developing children across varying SNR and word length. Methods: The study included forty two participants which were further subdivided into subgroup one consisting of 22 typically developing children aged 6-7.11 years (SGI) and 20 typically developing children aged 8-10 years in subgroup two (SGII). Development of Hindi word identification in noise test for children (HWINT-C) involved multi-step processes including selection of words, familiarity rating, and content validation, internal consistency and test-retest reliability. The test included bisyllabic and monosyllabic words recorded by a native Hindi female speaker presented in eight-talker babble at +5 dB and +7 dB SNR administered dioticallyat 65 dB SPL. Results: The developed HWINT-C in this study demonstrated to have high internal consistency and test-retest reliability. Typically developing children in the older group (SGII) significantly outperformed the younger group (SGI), Additionally performance improved with increasing signal-to-noise ratio (SNR) in both SGI and SGII, but no significant differences were found across word lengths. Conclusions: The HWINT-C test is a reliable and valid tool for assessing word-in-noise perception in children. Age-related trend was observed, where performance improved with age, Similar findings were observed with increase in SNR, emphasizing need of favorable conditions in younger population.